Floral mimicry in Oncidioid orchids - Powell, Martyn P. (Universidad de Costa Rica, 2016)
Extensive radiation in oncidioid orchids (subtribe Oncidiinae) has resulted in over 1,700 species in tropical America in some 70 genera. They exhibit a wide range of habitats, occurring terrestrially or, more commonly, epiphytically and can be found from sea level to the Andean paramós and from deserts to rainforests.